Cardiovascular morphometry with high-resolution 3D magnetic resonance: First application to left ventricle diastolic dysfunction. (September 2017) - Gallo, Diego; Vardoulis, Orestis; Monney, Pierre; Piccini, Davide; Antiochos, Panagiotis; Schwitter, Juerg; Stergiopulos, Nikolaos; Morbiducci, Umberto
Highlights: A morphometric analysis is performed on diastolic dysfunction patients and healthy age-matched controls. Morphometric differences are found not only in left ventricle region, but also in the downstream aorta. In patients, the aorta is found to be more distorted in terms of curvature and torsion. Aortic volume and arch width are significantly different between patients and controls. The observed morphometric differences might imply differences in hemodynamics, by virtue of the influence of geometry on blood flow patterns. The identified geometric parameters might help to determine early aortic geometric alterations, and potentially prevent evolution toward dysfunction. Abstract: In this study, an image-based morphometry toolset quantifying geometric descriptors of the left ventricle, aorta and their coupling is applied to investigate whether morphological information can differentiate between subjects affected by diastolic dysfunction (patient group) and their age-matched controls (control group). The ventriculo-aortic region of 20 total participants (10 per group) were segmented from high-resolution 3D magnetic resonance images, from the left ventricle to the descending aorta. Each geometry was divided into segments in correspondence of anatomical landmarks. The orientation of each segment was estimated by least-squares fitting of the respective centerline segment to a plane. Curvature and torsion of vessels' centerlines were automatically extracted, and aortic arch was characterized in terms of height and width. Tilt angle between subsequent best-fit planes in the left ventricle and ascending aorta regions, curvature and cross-sectional area in the descending aorta resulted significantly different between patient and control groups ( P -values < 0.05). Aortic volume ( P  = 0.04) and aortic arch width ( P  = 0.03) resulted significantly different between the two groups. The observed morphometric differences underlie differences in hemodynamics, by virtue of the influence of geometry on blood flow patterns. The present exploratory analysis does not determine if aortic geometric changes precede diastolic dysfunction, or vice versa. However, this study (1) underlines differences between healthy and diastolic dysfunction subjects, and (2) provides geometric parameters that might help to determine early aortic geometric alterations and potentially prevent evolution toward advanced diastolic dysfunction.